1999
DOI: 10.1038/sj.onc.1202664
|View full text |Cite
|
Sign up to set email alerts
|

Functional localization of a melanoma tumor suppressor gene to a small (≤2 Mb) region on 11q23

Abstract: We have previously demonstrated the existence of a melanoma tumor suppressor gene(s) on the long arm of chromosome 11 through suppression of tumorigenicity assays. Although loss of heterozygosity studies also support this ®nding, only a large critical region (44 cM) has been identi®ed to date on 11q22-25. To further localize a tumor suppressor gene(s) within this region, we have now generated and characterized nine melanoma microcell hybrids, each retaining an introduced fragment of 11q. Of the nine hybrids, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…Our data demonstrate that 89% of the informative cases displayed losses at this region and indicate that a putative TSG mapping within or near the D11S2000 locus is critical for the development of NPC. A recent report by Robertson et al (1999) suggests that a more precise location for this locus is 11q22.3-23.1. The previous LOH studies suggested that the common deletion region in NPC is at 11q22-24.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our data demonstrate that 89% of the informative cases displayed losses at this region and indicate that a putative TSG mapping within or near the D11S2000 locus is critical for the development of NPC. A recent report by Robertson et al (1999) suggests that a more precise location for this locus is 11q22.3-23.1. The previous LOH studies suggested that the common deletion region in NPC is at 11q22-24.…”
Section: Discussionmentioning
confidence: 95%
“…The D11S1647 marker overlaps with D11S2000, but was not informative in these cell lines. Other than NPC, a deletion at 11q22-23 has been reported in a variety of carcinomas, including melanoma (Robertson et al, 1999), breast (Carter et al, 1994), ovarian (Foulkes et al, 1993), lung (Rasio et al, 1995), cervical (Bethwaite et al, 1995), bladder (Shaw et al, 1995), colorectal (Keldysh et al, 1993), and prostate cancers (Dahiya et al, 1997). Molecular analysis of the chromosome 11 tumor segregants clearly indicates the existence of at least two putative TSGs residing on the long arm of chromosome 11, which may be critical to the development of NPC.…”
Section: Discussionmentioning
confidence: 99%
“…21,29 Our finding of substantial LOH in the 11q21-23 region for in-transit lesions is in agreement with others suggesting this loss is a later event in tumor progression and may more likely be involved in tumor metastasis rather than cancer initiation. 26,30 LOH on chromosome 1p in early stage tumors is a rare event. 25 However, we found significant LOH in this region in in-transit metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Furthermore, because advanced metastasis may contain additional LOH events (ie, distal arm of 1p and 11q23) not identified or infrequent in primary tumors, the role of these findings is unknown. 25,26 Particularly, of interest is at which point in the course of tumor progression do these events occur and are they clinicopathologically relevant. Identification of those genetic events associated with early stages of metastasis offers the advantage of establishing potential tumor markers to assess patient risk and monitor subclinical disease.…”
mentioning
confidence: 99%
“…All but one of the non-random breakpoints we selected using Brodeur's method are on chromosomes 1, 6, 7, 9 and 11, in good agreement with the established consensus. Among the studies that support some of the speci"c regions we selected are two studies Robertson et al, 1999) suggesting that there is one or more tumor suppressor genes on 11q2, and a cell fusion study of Trent et al (1990). The cell fusion study showed that the introduction of a normal chromosome 6 into a human melanoma cell line with a deletion in the long arm of the chromosome resulted in altered cell morphology and decreased cloning e$ciency, suggesting the presence of a tumor suppressor gene on chromosome 6.…”
Section: Discussionmentioning
confidence: 99%